A Series of Dipeptide Derivatives Containing (S)‐5‐Oxo‐pyrrolidine‐2‐carboxilic Acid Conjugates: Design, Solid‐Phase Peptide Synthesis, in vitro Biological Evolution, and Molecular Docking Studies. Issue 48 (21st December 2022) - Tivari, Sunil R.; Kokate, Siddhant V.; Gayke, Manoj S.; Ahmad, Iqrar; Patel, Harun; Kumar, Siva G.; Jadeja, Yashwantsinh S.
Abstract: Utilizing the solid phase peptide synthesis protocol, we have designed and prepared a novel dipeptide library containing (S)‐5‐oxopyrrolidine‐2‐carboxylic acid moiety. All the newly synthesized dipeptides were characterized by spectroscopic techniques as well as elemental analysis. Furthermore, the in vitro antimicrobial activities of the synthesized dipeptide conjugates were evaluated. Two Gram‐positive ( Streptococcus pyogenes and Staphylococcus aureus ) and two Gram‐negative bacteria ( Escherichia coli and Pseudomonas aeruginosa ) were utilized to evaluate the antibacterial activity of the screened derivatives. In contrast to the standard drug Ampicillin, the targeted derivatives exhibited good antibacterial activity. Additionally, two fungi ( Candida albicans and Aspergillus niger ) were used to evaluate the antifungal activity of the target dipeptides. The targeted derivatives also exhibited good antifungal activity compared to the standard drug Nystatin. In continuous, the molecular docking study of the targeted derivatives was also carried out, which revealed that the dipeptide analogs showed encouraging binding interaction networks with Escherichia coli DNA gyrase B and lanosterol‐14 alpha demethylase resulting in antibacterial and antifungal activities, respectively. Such synthesis, biological evolution, and molecular docking study of peptide derivatives with oxopyrrolidine conjugates open the door for the future development of new therapeutics containing heterocycle and peptide hybrids with potency as antimicrobial agents. Abstract : We have designed and prepared a novel dipeptide library containing (S)‐5‐oxopyrrolidine‐2‐carboxylic acid moiety. All the newly synthesized dipeptides were characterized by the spectroscopic techniques. Furthermore, the in vitro antimicrobial activities of the synthesized dipeptide conjugates were evaluated. When compared to the standard drug Ampicillin, compounds 6c‐e, 6 g, 6i, and 6j displayed good to moderate activity in contrast to the bacterial strain E. c . Furthermore, when compared to the standard drug Nystatin, derivatives 6c‐e and 6j exhibited good to moderate antifungal activity against the fungal strain C. a . Overall, it has been observed that the compounds 6 e and 6 g exhibited better activities against both bacterial and fungal strains. Addition of histidine (6 e ) and cysteine (6 g ) to the peptide chain significantly increased the microbial activity of the respective derivatives against both bacterial and fungal strains. Molecular docking studies of cyclic peptide derivatives against DNA gyrase and lanosterol 14‐alpha demethylase showed a correlation between biological activity and docking score.